2004
DOI: 10.1038/modpathol.3800024
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus plays no role in the tumorigenesis of small-cell carcinoma of the lung

Abstract: Epstein-Barr virus infection has been associated with lymphoepithelioma-like carcinoma of the lung in Asian patients. Recently, Epstein-Barr virus proteins or genomic DNAs were detected in pulmonary squamous-cell carcinoma, adenocarcinoma, and undifferentiated small-cell carcinoma in American patients. We studied 23 cases of small-cell carcinoma of the lung for evidence of Epstein-Barr virus infection by in situ hybridization, immunohistochemistry, and polymerase chain reaction methods. Of the 23 cases, 13 cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 27 publications
1
17
0
2
Order By: Relevance
“…Two previous serologic studies found a higher seroprevalence of several EBV antibodies in lung cancer cases compared with healthy controls (Desgranges and de-The, 1979; Roy et al , 1994). Among tissue-based studies, some studies have found 5–10% positivity by EBER ISH or EBV nuclear antigen IHC (Kasai et al , 1994; Wong et al , 1995; Grinstein et al , 2002), whereas others have found no positivity by EBER ISH (Conway et al , 1996; Kijima et al , 2001; Hayakawa et al , 2003; Chu et al , 2004; Lim et al , 2009) and generally low or no positivity by other markers (Chu et al , 2004). Although EBER ISH is considered the gold standard for detecting EBV-associated cancers because of its high abundance in latently EBV-infected cells, it is not a perfect measure (Delecluse et al , 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two previous serologic studies found a higher seroprevalence of several EBV antibodies in lung cancer cases compared with healthy controls (Desgranges and de-The, 1979; Roy et al , 1994). Among tissue-based studies, some studies have found 5–10% positivity by EBER ISH or EBV nuclear antigen IHC (Kasai et al , 1994; Wong et al , 1995; Grinstein et al , 2002), whereas others have found no positivity by EBER ISH (Conway et al , 1996; Kijima et al , 2001; Hayakawa et al , 2003; Chu et al , 2004; Lim et al , 2009) and generally low or no positivity by other markers (Chu et al , 2004). Although EBER ISH is considered the gold standard for detecting EBV-associated cancers because of its high abundance in latently EBV-infected cells, it is not a perfect measure (Delecluse et al , 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been implicated in ∼10% of gastric cancers (Young and Rickinson, 2004). Although lung cancer cases in serological studies had higher EBV seropositivity than healthy controls (Desgranges and de-The, 1979; Roy et al , 1994), previous studies of EBV in lung tumour tissue have generally produced negative results, except in rare cases of lymphoepithelioma-like carcinomas (LELCs) (Chu et al , 2004; Lim et al , 2009). However, previous studies largely tested for expression of EBV-encoded small RNA ( EBER ), which is generally abundantly expressed in cells with latent EBV infection but occasionally may be absent or heterogeneously expressed in EBV DNA-positive tumours (Iwakiri and Takada, 2010).…”
mentioning
confidence: 99%
“…A slightly higher frequency of EBER has been described in squamous cell carcinoma and neuroendocrine carcinomas (38). A subsequent study in small cell lung cancer however showed complete absence of EBER-1 by in situ hybridization (39) and no staining for ZEBRA and LMP-1 and only focal expression of EBNA-1. EBV was similarly absent in mesotheliomas and lung adenocarcinomas in the study by Conway et al (40).…”
Section: %) --------------------------------------------------------mentioning
confidence: 99%
“…Despite being associated with lymphoepithelioma-like carcinoma in the lung, mainly in Asian patients,27 different publications have failed to correlate EBV as a risk factor in the Western population. Koshiol et al 28 recently reported an evaluation of EBV miRNA, DNA, RNA and protein in adenocarcinoma and squamous cell lung carcinoma cases from Caucasian patients, showing little evidence of EBV in lung tumour.A lack of association has also been proposed in the tumourigenesis of small cell lung carcinoma 29…”
Section: Discussionmentioning
confidence: 99%